2018
DOI: 10.1108/bfj-02-2018-0122
|View full text |Cite
|
Sign up to set email alerts
|

Development of competences for teppanyaki chefs in food and beverage education

Abstract: Purpose The purpose of this paper is to focus on the development of competences for use by professional teppanyaki chefs in food and beverage education in Taiwan. Design/methodology/approach The research methodology includes the Delphi technique and incorporates interviews with three types of experts: instructors from culinary departments at a university, seasoned teppanyaki professionals and owners of teppanyaki establishments. An analysis of the responses provided by these industry experts led to identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Situated cognition asserts that conceptual learning is “situated” in the activities through which students acquire knowledge of the concepts being taught (Hickey et al. , 2020; Shyr et al. , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Situated cognition asserts that conceptual learning is “situated” in the activities through which students acquire knowledge of the concepts being taught (Hickey et al. , 2020; Shyr et al. , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other scholars also revealed that chefs must master food processing (Antun & Salazar, 2005;Bosselman, 2016;Johnston & Phelan, 2016;Zopiatis & Constanti, 2007). For instance, a study conducted by Shyr, Pan, Huang, and Chang (2018) states that a teppanyaki chef must have four competency dimensions consisting of knowledge, technique, affect and attitude. Zopiatis (2010) stated that this culinary expertise includes knowledge of foodservice operations, knowledge of culinary flavors, and knowledge of recipe and menu development.…”
Section: Culinary Expertisementioning
confidence: 99%
“…However, few studies have pointed out how chefs and suppliers affect a company's sales performance. Likewise, culinary innovation has always been important in restaurants (Genc and Kozak, 2020;Shyr et al, 2018). However, few studies have noted how restaurants can effectively improve their performance through chefs' tacit knowledge sharing.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have pointed out how chefs and suppliers affect a company's sales performance. Likewise, culinary innovation has always been important in restaurants (Genc and Kozak, 2020; Shyr et al. , 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation